Efektivitas Financial Leverage Sebagai Akibat Dari Kinerja Keuangan Rentan Dengan Pandemi Pada Bank Konvensional di Indonesia - Nur Amalina; Sajiwo Tri Prakoso; Kharisma Aulia Insani (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2023)
This study aims to examine the effect of leverage on financial performance. The data used in this study is secondary data from the financial reports of banking companies listed on the Indonesia Stock Exchange as of August 2019 -2021. In taking the sampling using purposive sampling technique. The analytical method used in this study is multiple regression analysis. The results of the study show that the Debt ratio and Debt to equity ratio have an effect on Return On Assets. Meanwhile, the Interest Covaregae Ratio has no effect on Return On Assets. For Debt to equity ratio and Interest Covaregae Ratio affect Return On Equity. Meanwhile, the Debt ratio has no effect on Return On Equity.